Yeast Rnt1p is required for cleavage of the pre-ribosomal RNA in the 3' ETS but not the 5' ETS. - Kufel, J (1999)
We have reexamined the role of yeast RNase III (Rnt1p) in ribosome synthesis. Analysis of pre-rRNA processing in a strain carrying a complete deletion of the RNT1 gene demonstrated that the absence of Rnt1p does not block cleavage at site A0 in the 5' external transcribed spacers (ETS), although the early pre-rRNA cleavages at sites A0, A1, and A2 are kinetically delayed. In contrast, cleavage in the 3' ETS is completely inhibited in the absence of Rnt1p, leading to the synthesis of a reduced level of a 3' extended form of the 25S rRNA. The 3' extended forms of the pre-rRNAs are consistent with the major termination at site T2 (+210). We conclude that Rnt1p is required for cleavage in the 3' ETS but not for cleavage at site A0. The sites of in vivo cleavage in the 3' ETS were mapped by primer extension. Two sites of Rnt1p-dependent cleavage were identified that lie on opposite sides of a predicted stem loop structure, at +14 and +49. These are in good agreement with the consensus Rnt1p cleavage site. Processing of the 3' end of the mature 25S rRNA sequence in wild-type cells was found to occur concomitantly with processing of the 5' end of the 5.8S rRNA, supporting previous proposals that processing in ITS1 and the 3' ETS is coupled.